KONSEPTUALISASI SISTEM PENDIDIKAN ISLAM: Belajar melalui Masa Keemasannya - Muh. Akib D. (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
Islam had its golden age in the history during the middle age. Progress in many aspects of life was of the clear signs especially that of science and knowledge of various disciplines with the very well known scholars of their time like Al-Kindi, Ibnu Sina, Al-Ghazali, and others. Those days the Muslims did not see the religi-ous and secular knowledge as a dichotomy. The zeal for wisdom was so high that they started many institutes and made such huge efforts to translate the scripts of the ancient Greek’s philosophy. In addition, great vehemence shown by all (the ruler as well as the people) had really become a common oath, which was for the universal glory of Islam.